Neutrophil gelatinase-associated lipocalin as a biomarker for acute kidney injury in children after cardiac surgery - Meta Herdiana Hanindita; Riskky Vitria Prasetyo; Ninik Asmaningsih Soemyarso; I Ketut Alit Utamayasa; Paul Tahalele (Indonesian Pediatric Society, 2016)
Background Acute kidney injury (AKI) is still diagnosed by measuring the estimated creatinine clearance (eCCl), despite the fact that it may not change until 50% or more of kidney function has been lost. AKI after cardiac surgery is related to prolonged intensive care, decreased quality of life, and increased long term mortality. Neutrophil gelatinase-associated lipocalin (NGAL) represents an early biomarker of AKI, which may be useful for assessing AKI in cardiac patients.Objective To determine the validity of urinary and plasma NGAL as biomarkers for AKI in children after cardiac surgery.Methods Subjects were children who underwent cardiac surgery in Dr. Soetomo Hospital, Surabaya, Indonesia from August 2013 to January 2014. Serial urine and blood samples were analyzed for NGAL before surgery, as well as at 2h, 4h, 12h, and 24h after surgery. The AKI was established based on pRIFLE criteria. Estimated creatinine clearance (eCCl) was calculated from the estimated glomerular filtration rate (eGFR), according to age by the traditional Schwartz formula. Serum creatinine was assayed by the Jaffe method before surgery, as well as at 12h, 24h, 48h, and 72h after surgery.Results Of 20 subjects, 5 developed AKI. Urinary and plasma NGAL increased markedly at 2h postoperatively, as compared to eGFR which showed a rise at 12-48 h after cardiac surgery. Analysis of 2h post-operative urinary NGAL at a cut off value of 11.270ng/mL yielded an area under the curve (AUC) of 1.00 (95%CI 2.63 to 12.13), with sensitivity and specificity of 100% each for AKI. In addition, 2h post-operative plasma NGAL at a cut off value of 8.385 ng/mL yielded an AUC of 1.00 (95%CI 3.71 to 12.15) with sensitivity and specificity of 100% each for AKI.Conclusion Urinary and plasma NGAL are valid as early biomarkers for AKI in children after cardiac surgery.